Rhyming in the Context of the Phonological Awareness of Pre-School Children - Soňa Grofčíková; Monika Máčajová (Center for Educational Policy Studies Journal)
Rhyming is one of the basic skills associated with phonological awareness. This paper aims to introduce theoretical starting points and the results of research into children’s rhyming in the context of phonological awareness. The text explains theoretical circumstances pertaining to the theme and defines key concepts. The main part of the paper includes the results of the research of pre-school children in Slovakia. There were 866 respondents (children) of 4 to 7 years of age. The subject of the research was the rhyming skills of children, which was tested in three independent areas: completing the rhyme in a nursery-rhyme, awareness of rhymes, and the production of rhymes.